PLAN DE MARKETING ESTRATÉGICO PARA LA EMPRESA AGROPECUARIO “EL FINQUERO” DE LA PARROQUIA MALACATOS, DEL CANTÓN LOJA 2018- 2021 - Alvarado Romero, Gina Catalina (2019)
The aim of the present investigation was to perform a Strategic Marketing Plan for the Company's Agricultural “The Farmer” of the parish of Malacatos, of Canton Loja, with the aim of establishing strategies that drive its development through a monitoring of the current situation in which it is located and thus be able to give way to the implementation of priority activities for its implementation. The research was supported by a theoretical framework in which consist the theoretical foundations necessary to carry out the Marketing Plan development, concepts based on the authors D'alessio Ipinza and Ricardo Hoyos Ballesteros ; in addition to this, the application of a methodology that facilitated to maintain a sequence and logical process in every aspect treaty, on the basis of an interview directed to the key personnel of the company (Manager and Employee), and surveys that were applied to their customers, tools that, once applied provided the analysis and interpretation of the results. In the Results it is given to know the interpretation of every one of the analysis, starting with the study PESTEC that deals with political factors, economic, social, technological and competitive environment, whose results led to the structuring of the matrix MEFE, resulting in a weighted value of 2,72 value that indicates that the company is giving an answer slightly higher than the average established. Among the opportunities are registered you should take advantage of the enterprise are: technological development, increased access to the internet as well as the variety and negotiation with the main suppliers among the threats are the large number of competitors, decline in purchasing power, high rates of interest, payment of taxes and high fines. Within the competitive analysis, through the development of the matrix MPC, is able to know who are the major competitors of the company, among which are the Megacentro Agricultural humblest farmer with a score of 4.17, occupying a leading position in the sector, 6 followed by a 3,96 value corresponding to the agricultural center The Farm, a relationship that is effected in terms of the competition located in the city of Loja. For its part, in the Parish of Malacatos is leading the sector the Agricultural Field with a value of 3,56 second place is The Sower, with a value of 3.37, and finally to be placed as the last competitor in the Agricultural The Farmer with a weighting 2.93. The information for the development of the internal analysis was obtained through the application of an interview and survey targeting the staff of the company, information that allowed to know the key strengths and these include the credibility and trust that has generated the company with its customers, management of affordable prices, location among its weaknesses consist of: distribution, non-productive space, lack of advertising, promotions, slight growth in sales, etc Later the information was in the matrix SPACER whose weighted value was of 2.48 indicating that the company has an average response to the opportunities and threats remains a need to maximize their strengths and in this way lessen the impact of your weaknesses so that you can compete successfully in the market. In the discussion presents the development of the SWOT matrix, which summarizes the internal and external analysis of the company, establishing a weighting and pairing of variables, generating solution strategies among which are: develop advertising through the various media (print, radio and social networks), to offer promotions with the purpose of encouraging the purchase of products and at the same time be able to make a difference before the competition, and implementation of a new service in the company (consulting veterinarian). On the basis of what mentioned above leads to the proposal of the strategic marketing plan and its contents, by proposing a vision, mission and the development of the strategic objectives among which are: to generate demand for agricultural products by using tools of 7 promotion, position the company in the market and improve the quality of the service that this offers. Finally once you have made the corresponding studies are presented, the relevant findings and recommendations that will be put to the consideration of the Manager that Owns the Agricultural center for later execution in this way we conclude that the company has important strengths that deserve to be potencializadas to counter their weaknesses with the firm purpose of carrying out of the best way your commercial activity.